Actuator line model using simplified force calculation methods - G. P. Navarro Diaz; A. D. Otero; A. D. Otero; H. Asmuth; J. N. Sørensen; S. Ivanell (Wind Energy Science, 2023)
To simulate transient wind turbine wake interaction problems using limited wind turbine data, two new variants of the actuator line technique are proposed in which the rotor blade forces are computed locally using generic load data. The proposed models, which are extensions of the actuator disk force models proposed by Navarro Diaz et al. (2019a) and Sørensen et al. (2020), only demand thrust and power coefficients and the tip speed ratio as input parameters. In the paper the analogy between the actuator disk model (ADM) and the actuator line model (ALM) is shown, and from this a simple methodology to implement local forces in the ALM without the need for knowledge of blade geometry and local airfoil data is derived. Two simplified variants of ALMs are proposed, an analytical one based on Sørensen et al. (2020) and a numerical one based on Navarro Diaz et al. (2019a). The proposed models are compared to the ADM using analogous data, as well as to the classical ALM based on blade element theory, which provides more detailed force distributions by using airfoil data. To evaluate the local force calculation, the analysis of a partial-wake interaction case between two wind turbines is carried out for a uniform laminar inflow and for a turbulent neutral atmospheric boundary layer inflow. The computations are performed using the large eddy simulation facility in Open Source Field Operation and Manipulation (OpenFOAM), including Simulator for Wind Farm Applications (SOWFA) libraries and the reference National Renewable Energy Laboratory (NREL) 5 MW wind turbine as the test case. In the single-turbine case, computed normal and tangential force distributions along the blade showed a very good agreement between the employed models. The two new ALMs exhibited the same distribution as the ALM based on geometry and airfoil data, with minor differences due to the particular tip correction needed in the ALM. For the challenging partially impacted wake case, both the analytical and the numerical approaches manage to correctly capture the force distribution at the different regions of the rotor area, with, however, a consistent overestimation of the normal force outside the wake and an underestimation inside the wake. The analytical approach shows a slightly better performance in wake impact cases compared to the numerical one. As expected, the ALMs gave a much more detailed prediction of the higher-frequency power output fluctuations than the ADM. These promising findings open the possibility to simulate commercial wind farms in transient inflows using the ALM without having to get access to actual wind turbine and airfoil data, which in most cases are restricted due to confidentiality.